The Lower Ordovician Konservat-Lagerstätte (Morocco): precise age calibration - Akodad, M.; Gutiérrez-Marco, J. C.; Lehnert, Oliver; Lefebvre, Bertrand; Martin, Emmanuel L. O.; Nowak, Hendrik; Servais, Thomas; Vandenbroucke, Thijs R. A.; Van Roy, Peter (2016)
Trabajo presentado en el International Geoscience Programme Project 653 Opening Meeting (2016), celebrado en Durham (Reino Unido), del 25 de septiembre al 1 de octubre de 2016 The Fezouata Biota from the Ordovician of Morocco is preserved in a Konservat-Lagerstätte of major importance, that is today considered as an Ordovician ‘Burgess Shale-type Lagerstätte.’ The exceptionally preserved biota occur at di erent intervals within the Fezouata Formation. This Early Ordovician (Tremadocian – Floian) formation is composed mostly of ne-grained siliciclastics and was deposited on the peri-Gondwanan shelf near the palaeo-South Pole. According to recent sedimentological studies (Martin et al., 2016; Vaucher et al., 2016), the benthic communities of the Fezouata Biota lived in an open-marine environment, in a relatively shallow setting (upper o shore to lower shoreface) above storm wave base. The Fezouata Lagerstätte-bearing beds were initially estimated as ranging from upper Tremadocian to upper Floian (Van Roy et al., 2010) and later restricted to the upper Tremadocian (Martin et al., 2016). Here we present new biostratigraphical results from several fossil groups, including graptolites, trilobites, acritarchs, chitinozoans and conodonts. These new data provide for the rst time a precise biostratigraphical calibration of the Fezouata Biota. Acritarchs of the sub-assemblages of the messaoudensis-tri dum assemblage con rm the late Tremadocian age of the oldest Lagerstätte-bearing beds and allow a correlation with other peri-Gondwanan localities (Nowak et al., 2016). New graptolite studies (Gutiérrez-Marco and Martin, 2016) allow a detailed view of the most complete Lower Ordovician graptolite succession known from the African continent. They also indicate that most Lagerstätte-bearing beds are present in the late Tremadocian, while another level of exceptional preservation occurs in the ?Baltograptus jacksoni graptolite Biozones of middle Floian age. The conodont assemblages are devoid of any warm/tropical and temperate ...